(untitled) (Journal of Tropical Pharmacy and Chemistry, 2025)
Analysis cyanide acid in Solanum melongena and Solanum quitoense L before and after boiling. Cyanide acid is esthabushed by argonometricm method (Volhard) with three times repetition, for each kinds of eggplants Solanum melongena L dan Solanum quitoense L. The research showed have endireated that before boiling the content of cyanide acid Solanum melongena L (Craigi eggplant 71,712 mg/kg, kopek eggplant 46,310 mg/kg, gelatik eggplant 0 mg/kg) and Solanum quitoense L (asam eggplant 30,434 mg/kg) after boiling, the cyanide acid to slop Solanum melongena (Craigi eggplant 19,321 mg/kg, kopek eggplant 6.620 mg/kg, gelatik eggplant 0 mg/kg and Solanum quitoense L (asam eggplant 3.445 mg/kg). There is significant content have been reduced of cyanide acid in Solanum melongena L dan Solanum quitoense L